HAMBATAN BELAJAR ANAK BERKEBUTUHAN KHUSUS (ABK) PADA PEMBELAJARAN INKLUSI DI SD - Dewi Niswatul Fithriyah; Nabila Mahfudhotin I.; Qoni’atul Athiyah; Siti Mahfudhotul Alfia; Putri Lestari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Inclusive education aims to provide equitable access to education for all learners, including children with special needs (CWSN). Nevertheless, its implementation still faces several obstacles that hinder the success of the learning process. This article aims to analyze the learning barriers in inclusive education, covering both internal and external obstacles as well as their impact on the motivation and engagement of CWSN. The approach used is a literature review of articles relevant to inclusive education. The findings of the study reveal that internal barriers, particularly cognitive, affective, language, and communication barriers, as well as external barriers such as teaching media and methods that are not aligned with the needs of CWSN, lead to a decrease in students' motivation, active participation, and academic progress. Therefore, it is important to implement a flexible and responsive inclusive learning strategy that addresses individual needs in order to improve the quality of learning at the elementary school level.